2017
DOI: 10.1007/s13300-017-0236-9
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Insulin Degludec Versus Insulin Glargine in Adults with Type 1 and Type 2 Diabetes Mellitus

Abstract: IntroductionTo estimate the cost-effectiveness of insulin degludec (IDeg) versus insulin glargine U100 (IGlar U100) and new-to-market basal insulin analogues in patients with diabetes in order to aid decision-making in a complex basal insulin market.MethodsA simple, short-term model was used to evaluate the costs and effects of treatment with IDeg versus IGlar U100 over a 12-month period in patients with type 1 (T1DM) and type 2 diabetes (T2DM) from the perspective of the UK National Health Service. New-to-mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 33 publications
2
38
0
Order By: Relevance
“…Previous trials have established the efficacy and safety of the combination of GLP‐1RAs and SGLT2 inhibitors; we have demonstrated the same in participants with T2D uncontrolled on SGLT2 inhibitors, albeit with a fixed‐ratio combination of GLP‐1RA and basal insulin, versus basal insulin, as an add‐on to SGLT2 inhibitor ± OADs.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Previous trials have established the efficacy and safety of the combination of GLP‐1RAs and SGLT2 inhibitors; we have demonstrated the same in participants with T2D uncontrolled on SGLT2 inhibitors, albeit with a fixed‐ratio combination of GLP‐1RA and basal insulin, versus basal insulin, as an add‐on to SGLT2 inhibitor ± OADs.…”
Section: Discussionsupporting
confidence: 54%
“…IDegLira is a fixed‐ratio combination of the basal insulin degludec and the GLP‐1RA liraglutide; the safety and efficacy of IDegLira have been demonstrated in a variety of patient populations in the DUAL clinical trial programme . In the DURATION‐8 and AWARD‐10 clinical trials, combined therapy with GLP‐1RAs and SGLT2 inhibitors in patients failing to achieve glycaemic control on metformin and SGLT2 inhibitor ± metformin, respectively, resulted in improvements in glycaemic control, with no unexpected side effects. Treatments belonging to the GLP‐1RA and SGLT2 inhibitor classes of medications exert their positive effects on patients by different, but complementary, modes of action.…”
Section: Introductionmentioning
confidence: 99%
“…The BRIGHT study found that equivalent glycaemic control was possible with degludec, at a 20% lower dose than that of glargine U300 . These results may suggest that there are potential economic benefits with the use of degludec vs glargine U300; however, this must be explored further in additional studies, with different healthcare systems and patient populations, to support the limited data currently available …”
Section: Discussionmentioning
confidence: 95%
“…Other CEAs of degludec vs glargine U100, from a public healthcare payer perspective, have reported similar findings; degludec is a dominant or cost‐effective treatment option in patients with T2D across treatment regimens, in each respective setting . To date, these have all been informed by data from phase 3, treat‐to‐target clinical trials that have focused on the short‐term effects of hypoglycaemia rates and insulin dosing over a 1‐year time horizon in a European setting .…”
Section: Discussionmentioning
confidence: 79%
“…17 Prior to the DEVOTE trial, CEAs of degludec compared with glargine U100 captured the effects of hypoglycaemia rates and insulin dosing over a short-term (1-year) time horizon in patients with type 1 (T1D) or type 2 (T2D) diabetes, based on the phase 3 clinical trial programme. [18][19][20][21][22][23] The DEVOTE trial provided an opportunity to evaluate randomized, double-blind clinical trial data, including cardiovascular endpoints and death, in addition to severe hypoglycaemia rates and insulin dosing, to provide health economic analyses of degludec vs glargine U100 over a 2-year time horizon without extrapolation.…”
Section: Introductionmentioning
confidence: 99%